The Effect of Intangible Assets, Cash Holdings, and Advertising Investment on Startup Firm Value - Felensia Clara Santa Hendriyanto; Bagas Brian Pratama; Lalu Rahmat Sohdi (CV Edujavare Publishing, 2026)
Investor decisions are influenced not only by a company’s current financial condition but also by expectations regarding future business prospects. This study aims to examine the effect of intangible assets, cash holdings, and advertising investment on firm value in startup companies listed on the Indonesia Stock Exchange (IDX). This research is motivated by the tech winter phenomenon, which has led to declining startup funding and increased pressure on firms to maintain their value amid economic uncertainty. This study employed a quantitative approach using panel data regression analysis. The research sample consisted of technology-based startup companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2025 period that met the research criteria. Data were obtained from annual financial reports and analyzed using EViews 13. The dependent variable in this study is firm value measured by Tobin’s Q, while the independent variables consist of intangible assets, cash holdings, and advertising investment. The results show that intangible assets do not significantly affect firm value. Meanwhile, cash holdings have a significant positive effect on firm value, whereas advertising investment has a significant negative effect on firm value. These findings indicate that liquidity plays an important role in enhancing startup firm value, while excessive advertising spending may negatively influence market perceptions during periods of economic uncertainty.